1978
DOI: 10.1073/pnas.75.5.2234
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine, vasopressin, glucagon, and A23187 induce efflux of calcium from an exchangeable pool in isolated rat hepatocytes

Abstract: Isolated rat hepatocytes do not actively accumulate Ca2+ during prolonged incubation in vitro; however, these cells do exhibit a limited exchange of intracellular with extracellular Ca2+. The exchangeable pool represents about 2 nmol of CaS+ per mg of protein. In medium containing either a low (20 MM) or high (1 mM) concentration of Ca2+, the divalent cation ionophore, A23187 (at concentrations of 0.03-0.1 nmol/ mg of protein), causes release of 42Cad+ from this exchangeable pool but does not allow net influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(59 citation statements)
references
References 30 publications
(13 reference statements)
3
56
0
Order By: Relevance
“…The present paper describes the effects of the same agents on the efflux ofenergetically accumulated Ca2+ from rat heart mitochondria. Another thiolspecific reagent, namely N-ethylmaleimide, has also been reported as inducing a loss of Ca2+ from energized mitochondria (Lofrumento & Zanotti, 1978;Chen et al, 1978). These effects of mercurials and N-ethylmaleimide suggest that free thiol groups are required to maintain the membrane in a nonleaky state, and it is this that we have investigated.…”
mentioning
confidence: 83%
“…The present paper describes the effects of the same agents on the efflux ofenergetically accumulated Ca2+ from rat heart mitochondria. Another thiolspecific reagent, namely N-ethylmaleimide, has also been reported as inducing a loss of Ca2+ from energized mitochondria (Lofrumento & Zanotti, 1978;Chen et al, 1978). These effects of mercurials and N-ethylmaleimide suggest that free thiol groups are required to maintain the membrane in a nonleaky state, and it is this that we have investigated.…”
mentioning
confidence: 83%
“…These results led to the suggestion that an increased inflow of Ca to the cell is responsible for the increased concentration of cytoplasmic Ca (Assimacopoulos-Jeannet et al 1977;Keppens et al 1977). However, the results of further experiments showed that a-agonists can stimulate glycogen phosphorylase in the absence of extracellular Ca (Blackmore, Brumley, Marks & Exton, 1978), and induce a loss of Ca from liver cells Blackmore, Dehaye, Strickland & Exton, 1979a;Blackmore, Dehaye & Exton, 1979b;Chen, Babcock& Lardy, 1978) and, in particular, from the mitochondria (Blackmore et al 1979a b; Babcock, Chen, Yip & Lardy, 1979). Consequently, Blackmore et al (1979b) have proposed that x-agonists increase the concentration of cytoplasmic Ca principally by stimulating the release of Ca from mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the cytoplasmic Ca concentration is consistent with the proposal that the activation of glycogen phosphorylase kinase by x-agonists is mediated by an increase in the concentration of Ca in the cytoplasm which surrounds this enzyme . a-Agonists have been shown to cause a net loss of Ca from liver cells Chen et al 1978;Banks, Brown, Burgess, Burnstock, Claret, Cocks & Jenkinson, 1979), and evidence that mitochondrial Ca contributes to the bulk of this loss has been presented (Blackmore et al 1979a, b;Babcock et al 1979). The present results, in which a completely different technique has been used to show that adrenaline causes a loss of Ca from a kinetically defined intracellular compartment of exchangeable Ca, which includes mitochondrial Ca, are consistent with the observations of Blackmore et al (1979b) and Babcock et al (1979).…”
Section: Effects Of Adrenalinementioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence indicates that this is due to the release of Ca2+ from the mitochondria and endoplasmic reticulum (Chen et al, 1978;Babcock et al, 1979;Blackmore et al, 1979;Murphy et al, 1980;Barritt et al, 1981b;Berthon et al, 1981) and enhancement of Ca2+ inflow across the plasma membrane (Keppens et al, 1977;Assimacopoulos-Jeannet et al, 1977;Foden & Randle. 1978;Barritt et al, 1981b).…”
mentioning
confidence: 99%